Evaluating physical outcomes in elderly sport and dance rollator users - Niharika Bandaru; Anita Hökelmann; Abdelaziz Triki; Ulrich Thiel (Annales Kinesiologiae, 2024)
The present single-arm pilot study investigates the effects of a video-based dance intervention on physical outcomes in elderly individuals utilizing sports and dance rollators. In addition, the dance videos used in the current study are intended to integrate into the future Intercommunication Technology (ICT)-Rollator for the elderly. The aim is to evaluate the physical outcomes (such as gait, balance, mobility, and hand grip strength) during guided movement training (dance) using a video projected in a laboratory setting. The pilot study involved six elderly rollator users (aged 85 and above). In the initial assessment, subjects were screened for mobility and coordination limitations prior to pre-testing using a four-square-step test and the SF-36 questionnaire. Both pre-testing and post-testing included assessments of mobility, balance, and spatiotemporal gait parameters using the Timed Up-and-Go (TUG) test, Berg Balance Scale (BBS), and the Optogait system, respectively. Hand grip strength was measured using a hand dynamometer and reaction time was measured using a pipe-drop test. Blood pressure was monitored every 15 minutes during the training sessions to prevent adverse events, maintaining an upper range of 140-150/90-96. Adherence rates were measured based on the total duration of activity, calories burned per session, and dropout rates. Post-session questionnaires were administered to verify the respondents' qualitative evaluations of their degrees of exhaustion, enjoyment, impediments, facilitators, and suggested changes. The intervention included heart rate monitoring, which revealed gradual and slight increases in heart rate intensity and gradual decreases in heart rate ranges (HRR) during the dance sessions. The results indicate improvements in balance, mobility, gait, and adherence rates. Future longitudinal research will further examine the effectiveness of the dance intervention using the ICT-Rollator, comparing it to a control group using a conventional rollator. The ICT-Rollator could be a unique rehabilitation aid for the elderly, offering promising improvements.